Unit of account or medium of exchange? - Yeager, Leland (PSL Quarterly Review, 2012)
Article originally published in the volume 60 issue 241 of Banca Nazionale del Lavoro Quarterly Review (also known as BNL Quarterly Review). Money evolved gradually as a cuitural product; it was not orig-inally invented and imposed by the state (although it did Iater come under state domination). Historical evidence does not conclusively settle whether unit of account (numéraire) or medium of exchange evolved earliest. Quite plausibIy, one function carne first in some times and places, the other in others. Little of analytical importance hinges on the answer. Both functions are important in economie life and in monetary theory. Who knows how to measure and compare degrees of importance? IndirectIy or directly, as explained above, both functions have a quantitative aspect. Convenience does recommend a single numéraire within a currency area, but a well organized payments system can readiIy accommodate multiple media of exchange (if, indeed, notes and deposits of different banks and claims on other types of financial institution count as separate media). Much can be said in favor of separation of functions in the sense of a numéraire defined inde-pendently of any partieular medium of exchange. JEL Codes: E40